Explorations in critical criminology in honor of William J. Chambliss - Chambliss, William J.; Rothe, Dawn; Collins, Victoria E. (Studies in critical social sciences, 2019)
Front Matter -- Copyright Page -- Preface -- Figures and Tables -- Notes on Contributors -- Toward a Sociology of Organizational Criminal Conspiracies /William J. Chambliss and Christopher J. Moloney -- Organized Crime and the Sociological Imagination /Gary Potter -- Notes on the Art of Deception: the Crime Ethnography of William J. Chambliss /Mark S. Hamm and Jeff Ferrell -- Kate’s Law: the Social Construction of Crime in the Trump Era /Teresa C. Kulig and Francis T. Cullen -- Old Wine, New Bottles: Contextualizing Trump’s Regulatory Rollback /Raymond Michalowski and Meredith Brown -- ‘Blood for Oil’: Analyzing America’s War for the Greater Middle East as a Climate Crime of Empire /Ronald C. Kramer -- Green State Crimes and Toxic Prisons: Synthesizing Environmental Harms at the Intersection of the Military and Prison Industrial Complexes /Elizabeth A. Bradshaw -- Make Our Enemy—Kill Our Enemy: the Creation of the Islamic State of Iraq and Syria: From Realpolitik to Biopolitics to Necropolitics /Sarah Pedigo Kulzer and David O. Friedrichs -- Whose Law? What Order? Struggles within Juridical Fields /Ida Nafstad and Isabel Schoultz -- Back Matter -- Index.